2002
DOI: 10.1074/jbc.m202635200
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Organization of Bacteriorhodopsin in Model Membranes

Abstract: Bacteriorhodopsin is a proton-transporting membrane protein in Halophilic archaea, and it is considered a prototype of membrane transporters and a model for G-protein-coupled receptors. Oligomerization of the protein has been reported, but it is unknown whether this feature is correlated with, for instance, light activation. Here, we have addressed this issue by reconstituting bacteriorhodopsin into giant unilamellar vesicles. The dynamics of the fully active protein was investigated using fluorescence correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 46 publications
5
40
1
Order By: Relevance
“…However, we did not observe any appreciable difference with the corresponding lifetimes measured for dark adapted membrane. Our observation contrasts with the results of Kahya et al who reported a decreased lateral mobility for photo-activated bR molecules due to formation of clusters comprising two or three trimers (Kahya et al, 2002). Their results, however, relied on fluorescence correlation spectroscopy and freeze-fracture electron microscopy of bR reconstituted in model membranes (giant unilamellar vesicles).…”
Section: Quantitative Analysis Of Intertrimer Interaction Energycontrasting
confidence: 99%
“…However, we did not observe any appreciable difference with the corresponding lifetimes measured for dark adapted membrane. Our observation contrasts with the results of Kahya et al who reported a decreased lateral mobility for photo-activated bR molecules due to formation of clusters comprising two or three trimers (Kahya et al, 2002). Their results, however, relied on fluorescence correlation spectroscopy and freeze-fracture electron microscopy of bR reconstituted in model membranes (giant unilamellar vesicles).…”
Section: Quantitative Analysis Of Intertrimer Interaction Energycontrasting
confidence: 99%
“…In the first (17), the mobilities of MscL [R ϭ 25 Å (18)] and LacS [R ϭ 32 Å (19)] differ by a factor of 1.3 corresponding to the ratio of their radii. In the second (14), a 1͞R law fits correctly the data obtained by FCS and freeze-fracture electron microscopy on photo-activated, oligomerized BR.…”
Section: Resultssupporting
confidence: 65%
“…In the Gibbs formulation some of the physical consequences of the force-dipole model become clearer than in the semi-microscopic formulation. One of these consequences is an influence of the activity on the tension of the membrane, which is discussed in section V. Another consequence of the force-dipole model, discussed in section VI, is a hydrodynamic interaction force between the membrane proteins induced by the activity, offering a possible explanation of two experiments reported in [10] on the clustering and diffusion of active bacteriorhodopsin molecules. A conclusion is given in section VII, and finally an appendix is added where the bulk hydrodynamics is solved directly for the semi-microscopic formulation in the case of a nearly planar membrane.…”
Section: Introductionmentioning
confidence: 94%